Counterfactual Thinking in Tourette's Syndrome: A Study Using Three Measures. (27th November 2014) - Zago, Stefano; Delli Ponti, Adriana; Mastroianni, Silvia; Solca, Federica; Tomasini, Emanuele; Poletti, Barbara; Inglese, Silvia; Sartori, Giuseppe; Porta, Mauro
Abstract : Pathophysiological evidence suggests an involvement of frontostriatal circuits in Tourette syndrome (TS) and cognitive abnormalities have been detected in tasks sensitive to cognitive deficits associated with prefrontal damage (verbal fluency, planning, attention shifting, working memory, cognitive flexibility, and social reasoning). A disorder in counterfactual thinking (CFT), a behavioural executive process linked to the prefrontal cortex functioning, has not been investigated in TS. CFT refers to the generation of a mental simulation of alternatives to past factual events, actions, and outcomes. It is a pervasive cognitive feature in everyday life and it is closely related to decision-making, planning, problem-solving, and experience-driven learning—cognitive processes that involve wide neuronal networks in which prefrontal lobes play a fundamental role. Clinical observations in patients with focal prefrontal lobe damage or with neurological and psychiatric diseases related to frontal lobe dysfunction (e.g., Parkinson's disease, Huntington's disease, and schizophrenia) show counterfactual thinking impairments. In this work, we evaluate the performance of CFT in a group of patients with Tourette's syndrome compared with a group of healthy participants. Overall results showed no statistical differences in counterfactual thinking between TS patients and controls in the three counterfactual measures proposed. The possible explanations of this unexpected result are discussed below.